2005
DOI: 10.1038/sj.onc.1208709
|View full text |Cite
|
Sign up to set email alerts
|

Id2 protein is selectively upregulated by UVB in primary, but not in immortalized human keratinocytes and inhibits differentiation

Abstract: Solar ultraviolet B (UVB) acts as both an initiator and promoter in models of multistage skin carcinogenesis. We found that, whereas UVB induces apoptosis in human papillomavirus-16 E6/7-immortalized keratinocytes, it inhibits markers of differentiation in human foreskin keratinocytes (HFK). Potential mechanisms for this differential response were examined by DNA microarray, which revealed that UVB alters the expression of three of the four human inhibitor of differentiation/DNA binding (Id) proteins that comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 85 publications
6
17
0
Order By: Relevance
“…Our data are in agreement with recent reports that Id2 abrogates girradiation-induced cell-cycle arrest in human keratinocytes (Baghdoyan et al, 2005), and that upregulation of Id2 by UVB stimulates proliferation and predisposes keratinocytes to carcinogenesis by preventing their normal differentiation program (Simbulan-Rosenthal et al, 2005). Significantly, among potential target genes, crosstalk affects expression of only some (such as Id2 or, to a lesser degree, CD44), but not other (such as cyclinD1, c-Myc or EGFR) genes.…”
Section: Discussionsupporting
confidence: 93%
“…Our data are in agreement with recent reports that Id2 abrogates girradiation-induced cell-cycle arrest in human keratinocytes (Baghdoyan et al, 2005), and that upregulation of Id2 by UVB stimulates proliferation and predisposes keratinocytes to carcinogenesis by preventing their normal differentiation program (Simbulan-Rosenthal et al, 2005). Significantly, among potential target genes, crosstalk affects expression of only some (such as Id2 or, to a lesser degree, CD44), but not other (such as cyclinD1, c-Myc or EGFR) genes.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with other work showing that Id2 is down-regulated in melanomas of the skin and eye (7,43) and that Id2 is capable of inhibiting epithelial differentiation in neural crest (25) and in keratinocytes (44). Our experiments predict the existence of an activator associated with the E-box2 element of the E-cadherin promoter that is inhibited by Id2.…”
Section: Discussionsupporting
confidence: 82%
“…DNA microarray analysis revealed that whereas UVB induced a downregulation of Id1 in both cell types, expression of Id2 was upregulated by 10-to 19-fold in primary KC, but not in immortalized cells. On the other hand, expression of Id3 was upregulated fivefold in the immortalized cells (Simbulan-Rosenthal et al, 2005). Consistent with these results, the increased expression of Id3 in immortalized cells, but not in primary KC, was confirmed by RT-PCR analysis ( Figure 1a) and at the protein level after immunoblot analysis (Figure 1b).…”
Section: Uvb Upregulates Id3 Expression In Hpv16supporting
confidence: 83%
“…Three of the four known human inhibitors of differentiation and DNA binding (Id) genes , a class of helix-loop-helix (HLH) transcriptional repressors involved in differentiation, proliferation, apoptosis, and carcinogenesis were found to exhibit significant changes in expression following UVB exposure. Whereas Id1 was downregulated in both primary and immortalized cells upon UVB exposure, Id2 was only upregulated in primary KC, while Id3 was only upregulated in immortalized KC (Simbulan-Rosenthal et al, 2005). We subsequently found that ectopic expression of Id2 in primary KC suppressed differentiation, similar to the effects of UVB, and that Id2 small interfering RNA (siRNA) blocked this UVB response, suggesting that UVB suppresses differentiation of primary KC at least in part via upregulation of Id2 (Simbulan-Rosenthal et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation